Analysis of static response of RC beams with NSM CFRP/GFRP rods (Fracture and Structural Integrity, 2021)
In this paper experimental results of investigation on reinforced concrete (RC) beams strengthened with the near surface method (NSM) are analyzed considering the response under bending tests on two beams. One of the RC beams was damaged by bending until the yield of reinforcement and successively strengthened with carbon fiber polymer (CFRP) rod, while the second beam was strengthened with glass-FRP rod. Both the beams have been subjected to bending tests until failure. Experimental diagrams and discussion on static response are presented in the paper. It also places a particular emphasis on the non-linear response of RC sections strengthened with CFRP and GFRP rods under bending moment beyond the first elastic behavior.
Keywords: RC beams; NSM; CFRP-GFRP rod; Static test